2021
DOI: 10.1097/bot.0000000000001971
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Reduction of Displaced Intra-articular Calcaneal Fractures Using a Sinus Tarsi Versus Extensile Lateral Approach

Abstract: Objective: To evaluate the difference in the quality of fracture reduction between the sinus tarsi approach (STA) and extensile lateral approach (ELA) using postoperative Computed Tomography (CT) scans in displaced intra-articular calcaneal fractures (DIACFs).Design: Retrospective.Setting: Level 1 and level 2 academic centers.Patients: Consecutive patients undergoing operative fixation of DIACFs with postoperative CT scans and standard radiographs.Methods: Patients were identified based on Current Procedural T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Only 1 patient required surgical debridement for acute infection, and 50% of the patients in their cohort required implant removal at mean 13 months postoperatively. Busel et al 9 found 7 of 36 DIACFs (19.4%) treated using STA were excellent and 13 of 36 (36.1%) were good in their series. Using the same grading criteria as those authors, our results demonstrate most achieved good or excellent reductions (85%) and most Sanders II were excellent.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Only 1 patient required surgical debridement for acute infection, and 50% of the patients in their cohort required implant removal at mean 13 months postoperatively. Busel et al 9 found 7 of 36 DIACFs (19.4%) treated using STA were excellent and 13 of 36 (36.1%) were good in their series. Using the same grading criteria as those authors, our results demonstrate most achieved good or excellent reductions (85%) and most Sanders II were excellent.…”
Section: Discussionmentioning
confidence: 87%
“…To mitigate soft-tissue challenges faced with the ELA, the STA is increasingly being used for treatment of DIACF, with reports of equivalent comparative outcomes. 5,7–9 Previous work has demonstrated that surgeon experience inversely correlates with complication rates. 16–18 This holds true for other complex fractures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,11,20 However, the STA, with its narrow field of exposure, can represent a challenge to inexperienced surgeons dealing with complex intra-articular fractures of the calcaneus, leading to inferior quality of reduction. 6 The current article will describe a step-by-step technical note to successful ORIF of DIACF using a minimally invasive STA.…”
Section: Introductionmentioning
confidence: 99%